(untitled) (Al-Academy, 2025)
Graphic design is an important vital tributary that represents a visual identity for a society, group, or even at the individual level through symbols, signs, or formal patterns. The research deals with part of the bohemian phenomenon that arose in Europe. The research problem is summarized in the following question: “What is the bohemian style and its implications in graphic poster design?” Contemporary? As for the goal of the research, it revolved around “revealing the reflections of the bohemian style in contemporary graphic design.” In the second chapter, the theoretical framework was divided into four axes: first, “bohemianism, the concept and origins, the second axis, the reasons for its emergence and spread, and then the second main axis, which is.” "Representations of Bohemianism in plastic art, and the last topic focused on" Manifestations of Bohemian reflection in graphic design. As for the third chapter, the researcher followed the descriptive approach by choosing four models that were analyzed according to the analysis form approved by a number of experts in the specialty. The researcher arrived at the conclusion in the fourth chapter. To the most important results: Firstly, the Bohemian style was embodied through elements within the design and structural vocabulary that are characterized by different characteristics. Then came the conclusions, the most important of which is first: “The plans and drawings represent various forms of effective means that convey the bohemian symbols within the design and give a cohesive impression of the bohemian visual identity.” Then the recommendations, and then a list of references and sources